Digital Transformation Enablers and Organizational Performance Effects: A Study of Global Capability Centres - Devagupthapu, Sunil (Digital Repository of Theses, 2025)
“Digital transformation” has become a critical driver of organizational success, particularly for Global Capability Centers (GCCs) operating in the IT sector. This study investigates the key factors enabling digital transformation through the lens of the “T-O-E (technological, organizational, and environmental) framework” and examines the “perceived risk” as moderator in this relationship. Additionally, it explores effect of digital transformation on GCC’s organizational performance, considering both financial and non-financial outcomes. Findings of study highlight the importance of “technological, organizational, and environmental factors” in shaping digital transformation outcomes. Technological factors, including infrastructure, readiness, and investment in advanced tools such as “artificial intelligence”, “big data analytics”, and “cloud computing”, provide foundational support for digital transformation. Organizational factors, particularly leadership support and a culture of adaptability, play a pivotal role in ensuring successful technology integration and driving alignment with strategic objectives. Environmental factors, such as competitive pressures and regulatory requirements, serve as external catalysts compelling organizations to adopt digital solutions. A key contribution has been identifying perceived risk as a significant moderator in the relation of technological factors and digital transformation. Concerns surrounding cybersecurity, financial feasibility, and system reliability weaken the positive influence of technological enablers, highlighting the need for robust risk management strategies. However, perceived risk does moderate the relations of organizational and environmental factors, suggesting that strong leadership, an innovation-driven culture, and external pressures can sustain digital transformation momentum despite uncertainties. The study also affirms positive influence of “digital transformation” on “organizational performance”. Financially, digital initiatives enhance sales growth, operational efficiency, and profitability. Non-financially, they improve customer satisfaction, employee engagement, and retention by fostering a digitally enabled work environment. These insights emphasize the necessity of a balanced approach, where GCCs not only invest in cutting-edge technologies but also address risk perceptions through proactive management strategies. By integrating digital transformation efforts with strategic objectives and mitigating perceived risks, GCCs can enhance their market positioning and long-term competitiveness. This research has valuable theoretical and practical implications, providing comprehensive framework for organizations to traverse digital transformation in IT sector.